Investigation of TSPO variants in schizophrenia and antipsychotic treatment outcomes. (January 2015) - Pouget, Jennie G; Gonçalves, Vanessa F; Nurmi, Erika L; P Laughlin, Christopher; Mallya, Karyn S; McCracken, James T; Aman, Michael G; McDougle, Christopher J; Scahill, Lawrence; Misener, Virginia L; Tiwari, Arun K; Zai, Clement C; et al.
Aim: TSPO is a neuroinflammatory biomarker and emerging therapeutic target in psychiatric disorders. We evaluated whether TSPO polymorphisms contribute to interindividual variability in schizophrenia, antipsychotic efficacy and antipsychotic-induced weight gain.Patients & methods: We analyzed TSPO polymorphisms in 670 schizophrenia cases and 775 healthy controls. Gene–gene interactions between TSPO and other mitochondrial membrane protein-encoding genes ( VDAC1 and ANT1 ) were explored. Positive findings were evaluated in two independent samples (Munich, n = 300; RUPP, n = 119).Results:   TSPO rs6971 was independently associated with antipsychotic-induced weight gain in the discovery (puncor = 0.04) and RUPP samples (p = 3.00 × 10 -3 ), and interacted with ANT1 rs10024068 in the discovery (p = 1.15 × 10 -3 ) and RUPP samples (p = 2.76 × 10 -4 ).Conclusion: Our findings highlight TSPO as a candidate for future investigations of antipsychotic-induced weight gain, and support the involvement of mitochondrial membrane components in this serious treatment side effect. Original submitted 20 August 2014; Revision submitted 3 November 2014